Kemandirian Ekonomi Pesantren : Studi Manajemen Kewirausahaan di Pesantren Albidayah Jember - Nuruddin, Nuruddin; Bani, Bani (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to describe and analyze the entrepreneurial management implemented at Pesantren Albidayah Jember in achieving the economic self-sufficiency of the pesantren. This research employs a qualitative approach with a field study design. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using Miles and Huberman's interactive model. The findings reveal that Pesantren Albidayah has successfully developed several business units based on local potential, such as agriculture, livestock farming, and food production, with active involvement of the students (santri). The pesantren’s entrepreneurship not only contributes to the institution's economic independence but also shapes the students’ character to be self-reliant and competitive. This study recommends strengthening business management capacity and expanding market networks to support the sustainability of the pesantren's economic independence.